Review of gender, socioeconomic status, and ethnic background considerations reported in active school travel intervention studies. (June 2021) - Medeiros, Alina; Buttazzoni, Adrian; Coen, Stephanie E.; Clark, Andrew F.; Wilson, Katherine; Gilliland, Jason
Abstract: Introduction: Trends over the last half century have shown that fewer children today are engaging in active modes of travel to and from school than in previous generations. Interventions promoting active school travel (AST) can be effective at reversing these trends and increasing rates of AST among children. This paper aims to explore (1) how studies of AST interventions have considered or framed multiple equity factors, namely those related to gender, socioeconomic status (SES), and ethnic background, in the design and evaluation of AST interventions, and (2) to what extent studies of AST interventions report these equity considerations in their analyses, outcomes, programming, and discussions. Methods: Six databases were used (BIOSIS Previews, GeoBase, PubMed, SCOPUS, SPORTDiscus, and Web of Science) to obtain AST literature published between 2010 and 2019 from around the world. The inclusion criteria applied in this review included a focus on an AST intervention for children (aged 5–19 years), quantitative results, and a primary outcome related to AST. A total of 69 papers were included in the review. Results: Across AST intervention studies, equity considerations were scarcely reported. Among the explicit mentions, gender and socioeconomic status were reported most often compared to ethnic background. Some papers reported differential effects among groups. Gender, SES, and ethnic background were, when reported, generally considered as variables that were controlled for within study samples. Conclusions: Suggestions to address equity within studies of AST interventions include reporting equity considerations made throughout the intervention and its evaluation in the published article. Using and reporting equity frameworks to develop AST interventions and conducting sub-group analyses during evaluation allows for greater assessment of equity effects and improved utility and applicability of the AST intervention. Ensuring the integration of equity into AST literature is needed to support evidence-based and equitable practices.